The contribution of Regional Centers of Expertise for the implementation of the 2030 Agenda for Sustainable Development. (10th November 2019) - Shulla, Kalterina; Leal Filho, Walter; Lardjane, Salim; Sommer, Jan Henning; Salvia, Amanda Lange; Borgemeister, Christian
Abstract: The implementation of the 2030 Agenda for Sustainable Development and the achievement of the 17 Sustainable Development Goals requires a fully integrated approach between sectors, disciplines, countries, and actors. On the fourth year of its implementation, the uptake of SDGs from non-state actors is increasing around the world, by developing engaging mechanisms for involvement at horizontal and vertical level. Considering that activation of existing partnerships is important for SDGs, in conjunction with creating new ones, this research has analysed the approach of global network of Regional Centers of Expertise on Education for Sustainable Development. An overview of involvement is done based on a survey data, by exploring collaboration in local, national and international scale. Through Hierarchical Classification Analysis, the networks are grouped into clusters with similar characteristics and discussions include challenges and potentialities for intensifying the contribution towards the 2030 Agenda. Graphical abstract: Image 1 Highlights: Networks and partnerships are slowly adopting to the 2030 Agenda, due to inssuficient resources and collabroation. Stronger involvement in international/national processes for SDGs would increase networks visibility and revitalization. Governance, leadership, partner organizations, affect the approach for specific Goals of Regional Centers of Expertise. RCEs confirm the indivisibility of the 2030 Agenda, despite their aim to influence policies though ESD, embraced in Targets 4.7.